MUTU LAYANAN PENDIDIKAN DASAR - Rizki Ananda; Mutiara, Chintya; Nur Haniza Syahira; Sakinah, Intan; Kurnia Pratama, Afdhal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article highlights the quality of basic education services in Indonesia as a primary focus of the government’s efforts to improve human resource quality. Various strategic measures have been implemented, including equitable distribution of facilities and infrastructure, enhancement of teacher quality, and expansion of education access for underserved communities. The adoption of technology and digital learning also plays a vital role in education transformation. By analyzing policies such as the New Student Admission (PPDB) and identifying existing challenges and solutions, this article aims to provide a comprehensive overview of the current state and development direction of basic education service quality in Indonesia.